Phosphorus concentration and air temperature measurements from Lake Constance as accompanying data to diatoms counts from sediment cores BO10/79 and BO10/81 - Manuela Milan; Nina Albrecht; Simone Wengrat; Frank Peeters; Martin Wessels; Dietmar Straile (PANGAEA, 2024)
This data provides accompanying data to sediment core diatom counts from Lake Constance. Phosphorus concentrations were sampled / estimated since 1952 in the center of the lake (station Fischbach–Uttwil) and provided by the Institut für Seenforschung, Langenargen, Germany. Regular year-round measurements are available since 1967. Phosphorus concentrations are given as total phosphorus concentrations during winter mixis in the whole water column (0-250 m) and summer (July, August, September) average concentrations in the upper 20 m of the water column for each study year. Annual average air temperatures (site: Bregenz) were downloaded from the HISTALP web site (https://www.zamg.ac.at/histalp/), and are provided as additional metadata.